A Multilevel Procedure at Urban Scale to Assess the Vulnerability and the Exposure of Residential Masonry Buildings: The Case Study of Pordenone, Northeast Italy - Marco Vettore; Marco Donà; Pietro Carpanese; Veronica Follador; Francesca da Porto; Maria Rosa Valluzzi (Heritage, 2020)
More than the 60% of the Italian residential building stock had already been built by 1974, when seismic codes were enforced on a minimal part of the country. Unreinforced masonry buildings represent most of that share, but they are typical for each region, in terms of both materials and structural configurations. The definition of ‘regional’, i.e., more specific, vulnerability and exposure models are required to improve existing forecast models. The research presents a new geographic information system (GIS)-based multilevel procedure for earthquake disaster prevention planning at urban scale; it includes multicriteria analysis, such as architectural types, structural vulnerability analysis, microzonation studies, and socio-economic aspects. The procedure has been applied to the municipality of Pordenone (PN), a district town of the Friuli–Venezia–Giulia region, in Northeast Italy. To assess the urban seismic risk, more than 5000 masonry residential buildings were investigated and common types within sub-municipal areas and exposure data were collected. Simplified mechanical analysis provided a ‘regional’ vulnerability model through typological fragility curves. The integration of results into GIS tool permitted the definition of cross-mapping among vulnerability, damage scenarios (conditional and unconditional) and exposure (seismic losses, casualties, impact), with respect to various earthquake intensities expected in the town. These results are presented at different scales: from the single building, to submunicipal area and to the entire town.